QuCode: A Novel Conceptual Description of Quantum Algorithms - Ketineni, Hrithik; Perkowski, Marek (Proceedings / International Symposium on Multiple-Valued Logic, 2024)
Conventional presentations of quantum algorithms overwhelmingly rely on mathematical formalism, posing an unnecessary barrier to conceptual understanding. The growing influence of quantum computing across diverse domains necessitates more accessible education on the subject. To engage a broader audience in quantum computing, we introduce a new approach for teaching quantum algorithms: drawing parallels to classical pseudocode. This approach, which we call "QuCode," is demonstrated through its application to several black box quantum algorithms: Deutsch-Jozsa, Bernstein-Vazirani, and Simon's algorithm.